ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI DAYA SAING PADA SENTRA INDUSTRI MAKANAN KHAS BANGKA DI KOTA PANGKALPINANG - Rulyanti Susi Wardhani; Yulia Agustina (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2012)
This study aims to determine the effect of capital, packaging, network, business development, and human resource to the competitive ability at central industry of Bangka’s food in Pangkalpinang.It used primary data with census method as the sampling technique. The number of samples were 68 respondents, analyzed by confirmatory factor. The results of study issue two factors. First, financial factor which has capital and business development variable. Second, marketing factor which has packaging and network variable. Keywords: Micro and Medium Enterprise, Capital, Business Development, Financial Factor, Packaging, Network, Marketing Factor